2017
DOI: 10.3390/ma10080951
|View full text |Cite
|
Sign up to set email alerts
|

A Continuum Damage Mechanics Model for the Static and Cyclic Fatigue of Cellular Composites

Abstract: The fatigue behavior of a cellular composite with an epoxy matrix and glass foam granules is analyzed and modeled by means of continuum damage mechanics. The investigated cellular composite is a particular type of composite foam, and is very similar to syntactic foams. In contrast to conventional syntactic foams constituted by hollow spherical particles (balloons), cellular glass, mineral, or metal place holders are combined with the matrix material (metal or polymer) in the case of cellular composites. A micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Models for fatigue life prediction of composite materials using continuum damage mechanics have been put forward and discussed by authors such as Chaboche [88], Bhattacharya [89] or Diel [90]. Owen and Bishop 540 [31] concluded that Paris's law was applicable to the glass-fibre-reinforced composites.…”
Section: The Case Of Progressive Damage Modelsmentioning
confidence: 99%
“…Models for fatigue life prediction of composite materials using continuum damage mechanics have been put forward and discussed by authors such as Chaboche [88], Bhattacharya [89] or Diel [90]. Owen and Bishop 540 [31] concluded that Paris's law was applicable to the glass-fibre-reinforced composites.…”
Section: The Case Of Progressive Damage Modelsmentioning
confidence: 99%
“…The cumulative damage variable D will be valued 1 when the specimen is destroyed, and calculate the maximum plastic strain ε p m and the cumulative plastic energy dissipation in the cyclic process, then the parameter λ can be obtained use Equation (3), so the value of λ can fitaccording to Equation (14) by the test data, and the fitting results are presented in Table 6. The parameters can be fitted according to Equations (8) and (9) by the results of low-cycle fatigue test.…”
Section: The Parameter λ Of Evolutionequation Of Damage Accumulationmentioning
confidence: 99%
“…In this condition, the welds under cyclic are prone to damage accumulation, which is observed to be a process that can cause immediate failure when the load is not large enough [13]. It should be pointed out that damage accumulation has such an important impact on the performance and service life of structure [14][15][16][17][18][19], and even several studies have focused on the damage detection of the construction structure and material [20][21][22][23][24], but there is little consideration of the weld damage accumulation in the study of seismic performance of steel tubular truss structure joints [25][26][27][28], and the difference of the constitutive relation between the welding material and base metal is often neglected. For instance, the research results of Wang [29] revealed that the welding material and its parent material of 304 L steel have different hardening laws and damage evolution laws under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…For further details regarding cycle jumping and relevant application areas, see e.g. [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%